(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
The purpose of this study was to assess the clinical and laboratory features of lipitension in patients treated at the clinic of the Bukhara State Medical Institute. The study included 74 patients with arterial hypertension, of whom 38 had concomitant dyslipidemia (lipitension). Comparative analysis showed that patients with lipitension more frequently exhibited obesity, elevated levels of total cholesterol, LDL, triglycerides, as well as higher blood pressure and signs of left ventricular hypertrophy